Exploring the Father’s Role in Determining Neonatal Birth Weight: A Narrative Review - Alessandro Libretti; Federica Savasta; Anthony Nicosia; Christian Corsini; Alberto De Pedrini; Livio Leo; Antonio Simone Laganà; Libera Troìa; Miriam Dellino; Raffaele Tinelli; Felice Sorrentino; Valentino Remorgida (Medicina)
Birth weight, which exhibits variability across different populations, is influenced by a mix of genetic, environmental, and dietary factors originating from both the mother and father. Maternal characteristics, including age, socioeconomic status, prior pregnancies, weight, height, and weight increase throughout pregnancy, have a substantial influence on fetal growth and the health of the infant. On the other hand, the influence of paternal characteristics on the weight of newborns is still not fully comprehended in a consistent manner. Birth weight is an important factor that can help predict various maternal complications, such as the probability of having a C-section, experiencing postpartum hemorrhage or infections. It can also indicate future health challenges like asthma, cognitive impairment, and chronic diseases such as hypertension and diabetes. Nineteen publications were found through a thorough search of the Medline, PubMed, and Scopus databases, which provide insights into how paternal variables contribute to variations in birth weight. Significantly, the age of the father was found to be associated with higher chances of preterm birth and having a smaller size for gestational age in premature infants, while full-term children were more likely to have a larger size for gestational age. In addition, there is a constant correlation between the height of the father and the birth weight of the child. Taller dads are more likely to have babies with a higher birth weight and a lower likelihood of being small for gestational age (SGA). Although there were some discrepancies in the data about the weight and BMI of fathers, it was found that the height of fathers played a significant role in determining the size of the fetus and the weight of the newborn. While there may be differences in the conducted studies, these findings provide valuable insights into the complex connection between parental characteristics and fetal development. This data can be utilized to enhance clinical treatment strategies and enhance our comprehension of outcomes for neonates. Further homogeneous investigations are required to conclusively validate and build upon these findings.